“When You Choose to be a Gangbanger, You Deserve Everything You Get”: victim Dichotomization, Fear, and the Problem Frame - Gushue, Kelsey (Journal of contemporary criminal justice, 2018)
Media framing of an event can have a significant impact on both reader response and public opinion. Through an examination of the deadliest gang-related murder to ever occur in British Columbia, the current study extends previous research by analyzing the influence of victim characteristics on the development of a problem frame. We analyze all newspaper articles published in the Vancouver Sun mentioning at least one of the murder victims between October 19, 2007, and December 31, 2016 (N = 210). Results suggest that journalists use a number of techniques when creating a problem frame, including victim differentiation, purposeful inclusion of sources, and use of specific language. We argue that the extensive coverage of the murders provided an opportunity for the media to develop a problem frame that dichotomized victims, capitalized on societal fear of crime, and, consequently, affected calls for policy change.